2020
DOI: 10.1002/marc.202000365
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Control over Partial Transesterification of Polyacrylate Homopolymers as Platform for Functional Copolyacrylates

Abstract: Only recently, post‐polymerization modification reactions of unactivated polyacrylates have been emerging as an attractive alternative to utilizing reactive monomers, enabling the synthetic upcycling of these widely applied polymers. Within this contribution, the triazabicyclodecene‐catalyzed transesterification of polyacrylates is reported, including the reaction kinetics and the broad scope for macromolecular design of functional copolyacrylates. More specifically, the transesterification is performed under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Recently, several research groups started exploring the catalytic upcycling of poly­(meth)­acrylates via transesterification and amidation. , Our group developed a direct amidation and transesterification protocol for the modification of polyacrylates by the application of catalytic bases. ,, Here, triazabicyclodecene (TBD) enables transesterification and amidation of the polymeric esters with alcohols and amines, respectively, yielding a wide variety of functional polyacrylates and polyacrylamides using PMA as an unactivated base polymer. In addition, this catalytic approach was also applied to poly­(2-alkyl-2-oxazoline)­s comprising 2-methoxycarboxypropyl-2-oxazoline …”
mentioning
confidence: 99%
“…Recently, several research groups started exploring the catalytic upcycling of poly­(meth)­acrylates via transesterification and amidation. , Our group developed a direct amidation and transesterification protocol for the modification of polyacrylates by the application of catalytic bases. ,, Here, triazabicyclodecene (TBD) enables transesterification and amidation of the polymeric esters with alcohols and amines, respectively, yielding a wide variety of functional polyacrylates and polyacrylamides using PMA as an unactivated base polymer. In addition, this catalytic approach was also applied to poly­(2-alkyl-2-oxazoline)­s comprising 2-methoxycarboxypropyl-2-oxazoline …”
mentioning
confidence: 99%
“…Although some research groups have demonstrated the successful transformation of non-activated esters and amines/alcohols, e.g. , poly(meth)acrylates, 30–37 poly(2-oxazoline)s, 38–43 understanding the reaction kinetics and the relationship between the polymer structure and properties of non-activated esters is still of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of polymers is an efficient strategy to synthesize functional macromolecules, 4 because the synthesis of monomers containing functional group(s) can be tedious, and in addition, the functional group of the monomer may influence the polymerization behavior. 5 There are two main approaches to the introduction of functional groups into polymers by means of polymer reaction: the reaction of a polymer containing a reactive side chain, such as activated ester 6 or azide group, 7 and the reaction of a conventional polymer 8 such as poly(methyl acrylate) (PMA) 5a,9 or poly(methyl methacrylate) (PMMA). 10 The transesterification of polyacrylates with alcohol is promoted by metal catalysts, including metal alkoxides, 9a-d,10a and organocatalysts 11 have also recently been used.…”
Section: Introductionmentioning
confidence: 99%